Measurement of axial and shear mechanical response of PDMS elastomers and determination of Poisson's ratio using digital image correlation - Satya Pal; Abir Bhattacharyya (Polymer Testing)
Measurement of stress-strain response under different deformation modes is important for developing constitutive models of soft polymers. However, such measurements on soft and compliant polymers are challenging using traditional techniques due to generation of unwanted stress concentrations leading to premature failure during loading. In this study, a non-contact digital image correlation (DIC) technique along with a novel experimental setup were used to accurately measure the strain field on a specimen surface subjected to finite strain. Polydimethylsiloxane (PDMS) elastomers of three different base polymer to hardener ratio were characterized under three different deformation modes— uniaxial compression, uniaxial tension, and simple shear—over strain rates ranging between 10−3/s–10−1/s. The resulting strain fields exhibited uniformity across all the deformation modes up to finite strains. While the lower strain rate experiments are minimally affected by strain acceleration and inertia effects, the specimens loaded under higher strain rate (10−1/s) are initially affected by strain acceleration during loading, which precluded reliable determination of Young's moduli and shear moduli from the initial slope of the stress-strain responses. The Poisson's ratio calculated from the ratio between measured axial and lateral strains was close to 0.5 at small strains, and exhibited a close match with that calculated from Young's modulus (E) to shear modulus (G) ratio (E/G), validating linear elasticity theory at small strains. The tangent moduli for all the compositions were found to be practically strain-rate insensitive in the region of steady strain rate.